The effect of Maleic Anhydride Grafted Polypropylene on Hygrothermal aging of Paper Sludge Filled Polypropylene /Ethylene Propylene Diene Terpolymer composites - Salmah, Husseinsyah; Che Mohd Ruzaidi, Ghazali; Supri, A. Ghani; I. Ismail (Universiti Putra Malaysia, 2010)
Organized by Universiti Putra Malaysia, 10th - 12th December 2007 at Impiana Cerating, Pahang.